Factors effecting reproduction and larval development of Ostrea angasi (Sowerby 1871) : advancing hatchery production - O'Connor, SJ (2016)
The flat or native oyster, Ostrea angasi (Sowerby, 1871), was once a conspicuous inhabitant of many coastal bays and estuaries in south eastern Australia and formed the basis of a thriving wild fishery. Overfishing led to population collapses in NSW, Victoria, Tasmanian and South Australia, which in turn saw local demand for oysters being met through the production of Sydney rock oysters and the introduced Pacific oyster. As markets have developed and factors such as disease have impacted the production of other oyster species, there has been a renewed interest in production of O. angasi within the southern states. O. angasi are sequential protandric hermaphrodites and larviparous, with brooding adults retaining larvae on the gill filaments in the brachial chamber for approximately half the larval life cycle. Wild catch of O. angasi spat is low and unreliable and the cultivation of this species is reliant upon hatchery production. To date production techniques for O. angasi have been loosely based on those used for Saccostrea glomerata and Crassostrea gigas, and have varied in success, with many hatcheries still reporting poor outcomes. In part this has arisen from a lack of systematic assessments of the fundamental variables that determine hatchery success. Specifically, improvements in O. angasi production output and reliability require an improved understanding of the reproductive biology of the species and knowledge of conditions required to optimise late larval development and metamorphosis. In the first instance hatchery production is underpinned by the reproductive biology and ecology of this species. Knowledge of the temporal frequency of reproduction within New South Wales (NSW) estuaries is essential for larval acquisition and the development of a hatchery program. To address this, oysters were sampled over a 12 month period, across four estuaries, and examined histologically to reveal marked differences in gametogenic patterns to that previously reported in the southern states of Australia. The ...